Surgical Management of External Hydrocephalus in a Calf - Vahora, Mohsin S.; Patel, Sanjay B.; Shukla, Preeti G. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Hydrocephalus is an accumulation of excessive fluid in dura matter or ventricles of the brain thereby leading  to the swelling of the cranium (Long, 2001). Congenital  hydrocephalus can be internal or external, and is mainly  due to abnormal development of the foetus during  pregnancy; however, hereditary, infectious, environmental  and nutritional factors can also predispose this condition  (Whitlock et  al., 2008). This condition has been reported  occasionally in the ewe, doe, mare, and sow, whilst it is rarely  seen in cattle and buffalo (Long, 2001; Sharda and Ingole,  2002; Dhami et  al., 2007; Saini et  al., 2019). Hydrocephalus  occurs mainly due to three reasons, as excessive production  of cerebrospinal fluid (CSF), defective absorption of CSF,  and interference in the passage of CSF. Hydrocephalus may  cause increased intracranial cerebral pressure, progressive  enlargement of the head, convulsions, mental disability,  and even death (Mausumi et al. 2014.).
Keywords: Crossbred male calf; Hydrocephalus; Surgery; Uneventful recovery